ANALYSIS OF MASONRY BEHAVIOR ON NON-ENGINEERED HOUSE BUILDING TOWARDS LATERAL DEFORMATION BY USING FINITE ELEMENT METHOD BASED ON GUIDELINE - SRI HENY HIDAYATI; Agoes Soehardjono; wisnumurti wisnumurti (Rekayasa Sipil, 2023)
This study is based on the abundant damaged house building during the earthquake. Wall is an important part of a non-engineered house. It is constructed by clay bricks and mortar. The damage happened to the house building is not separated from the specification of the clay bricks used. Dynamic simulation towards the non-engineered construction would reveal the displacement value that happened to the structure of mansory that applies the guidelines from SNI, ACI, and condition in the field. The dynamic simulation of an ordinary non-engineered house employed finite element method. The purpose of this research is to find out the mechanical performance of the mansory when the earthquake is occurring. The method implemented in this research is scientific analysis through collecting the available theories and data from the previous research. A scientific method is started with deciding a concept based on the events frequently and generally happened in the field which are also considered a novelty. The following step is conducting data analysis by using finite element method where the maximum deformation displacement value reached ux 0.008 cm, uy 0.044 cm and uz 0.008 cm. From the simulation it can be concluded that the biggest displacement happened to mansory constructed based on the field condition.